Implementation of Health and Safety Programs: Basis for the Development of Information Education Materials - Cabigcabig, Alicia Ann B.; Punzalan, Randy D. (Edukhasi: Jurnal Inovasi Pendidikan, 2025)
This study aimed to assess the level of implementation of health and safety programs and the challenges encountered towards an information education campaign material during the school-year 2024-2025. The study involved the teachers, parents, and stakeholders of the public elementary schools in the division of Cabuyao. It utilized the descriptive correlational research wherein the survey-questionnaires served as the main source of data to describe the level of implementation of health and safety programs, and the challenges faced. This study revealed that the three groups of respondents have assessed that the Key Programs related to health and safety such as the Hazard Drill, WiNS, Child-Friendly School Environment, National Drug Education Program are Implemented, while School-Based Feeding Program was Highly Implemented. It was also found out that the three groups of respondents have different assessments on the level of implementation of programs related to safety and health of learners. Further, it was also found out that all of the challenges encountered in the implementation of the key programs in safety and health are Serious. 4.there is a mixed relationship between the implementation of the key programs and projects and the challenges faced. The implementations of the key programs such as WinS, Child-Friendly School Environment and School-Based Feeding Program were found to have significantly related with specific challenges. Other programs and projects such as Hazard Drill, National Drug Education Program and the overall implementation showed no significant relationship with the challenges encountered. Notably, Child Friendly School Environment emerged as the key factor that influences multiple areas on the challenges encountered. It highlights its effective implementation.